On the future of ramp-up management. (November 2018) - Schmitt, Robert; Heine, Ina; Jiang, Ruth; Giedziella, Felix; Basse, Felix; Voet, Hanno; Lu, Stephen
Abstract: The aim of this paper is to present research hypotheses and practical implications on developing a novel ramp-up management approach facing recent challenges and trends in the field of agile production. Applying a mixed-method design based on a quantitative pre-study with 67 researchers and qualitative interviews with seven practitioners in ramp-up-relevant fields showed a consensus on the continuing importance of human factors for future ramp-up management. For managing ramp-up phases, real-time data infrastructure is central to support the learning and decision making process and thus to increase ramp-up agility. Along with this requirement, organizations are expected to have flatter hierarchical structures and be able to extend their product portfolio by implementing new technologies such as additive manufacturing.